2016
DOI: 10.1038/nature19766
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine BDNF–TrkB signalling within a single dendritic spine

Abstract: Brain-derived neurotrophic factor (BDNF) and its receptor TrkB are crucial for many forms of neuronal plasticity1, 2, 3, 4, 5, 6, including structural long-term potentiation (sLTP)7, 8, which is a correlate of an animal’s learning7, 9, 10, 11, 12. However, it is unknown whether BDNF release and TrkB activation occur during sLTP, and if so, when and where. Here, using a fluorescence resonance energy transfer-based sensor for TrkB and two-photon fluorescence lifetime imaging microscopy13, 14, 15, 16, we monitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
283
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 287 publications
(302 citation statements)
references
References 41 publications
16
283
1
2
Order By: Relevance
“…To test whether crosstalk requires BDNF–TrkB–Rac1 signalling, we first used partial pharmacological inhibition of this pathway. Although strong inhibition of BDNF signalling has been shown to impair sLTP 15 , we found that weak inhibition of this pathway with a low concentration (0.25 μg ml −1 ) of TrkB-Ig preserved sLTP (Δ V supra sustained = 58 ± 13% (mean ± s.e.m. ), in which V denotes spine volume), but attenuated crosstalk (Δ V sub sustained = 20 ± 8%), suggesting that BDNF is required for this process (Fig.…”
contrasting
confidence: 53%
See 3 more Smart Citations
“…To test whether crosstalk requires BDNF–TrkB–Rac1 signalling, we first used partial pharmacological inhibition of this pathway. Although strong inhibition of BDNF signalling has been shown to impair sLTP 15 , we found that weak inhibition of this pathway with a low concentration (0.25 μg ml −1 ) of TrkB-Ig preserved sLTP (Δ V supra sustained = 58 ± 13% (mean ± s.e.m. ), in which V denotes spine volume), but attenuated crosstalk (Δ V sub sustained = 20 ± 8%), suggesting that BDNF is required for this process (Fig.…”
contrasting
confidence: 53%
“…We found that removal of postsynaptic BDNF significantly attenuated Rac1 and Cdc42 activation during sLTP without affecting RhoA (Fig. 1f, g), and reduced the associated expression of sLTP 15 (Extended Data Fig. 5a, b).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Two-photon fluorescence lifetime imaging microscopy (2pFLIM), in combination with FRET biosensors, has been proven to be useful for imaging signaling cascades during structural and functional LTP (Harvey et al, 2008b, Lee et al, 2009, Murakoshi et al, 2011, Zhai et al, 2013, Bosch et al, 2014, Kim et al, 2015, Harward et al, 2016, Hedrick et al, 2016). When single spines are stimulated with glutamate uncaging or electrical stimulation, Ca 2+ influx through NMDA receptors triggers complex signaling cascades, including the activation of protein kinases and small GTPase proteins, in turn regulating actin polymerization and increasing spine volume and postsynaptic sensitivity to glutamate (Nishiyama and Yasuda, 2015).…”
Section: Introductionmentioning
confidence: 99%